Analysis of E-Procuement Problems in LPSE in the Field of Procurement of Goods and Services in Binjai City - Agiet Mutiara Rengganis; Andri Soemitra (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to determine the problem of e-procurement in the procurement of goods and services in the Procurement Services Section of the Regional Secretariat of Binjai City. The type of research used is qualitative research. The data analysis technique uses data collection steps, data reduction, data presentation, qualitative data verification, to draw conclusions. The results of the study show that the Procurement Services Section of the Regional Secretariat of the City of Binjai has started to implement but is still in the minimal category in its implementation, it is known that only some members or employees in the Department of Procurement of Goods and Services in the City of Binjai have at least had special training certifications, as SIM form to be able to take part in running the LPSE in Binjai City itself, coupled with non-civil servant employees and several contract employees who apparently lack expertise in science such as computers.